Analysis of Tilapia (Oreochromis Niloticus) Hatchery Business at PT. STP, Karawang, West Java - Catur Pramono Adi; Pola Sabar Tumohon Panjaitan; Budi Sulistiyo; Muhammad Yusuf; Aripudin; Mohammad Ismail; Bagus Oktori; Mukhlis (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to analyze the cost and revenue structure and evaluate the financial feasibility of the tilapia (Oreochromis niloticus) seed production (hatchery) business. The breeding stage is a crucial early phase in the aquaculture production cycle. The feasibility evaluation encompassed calculations of the Revenue to Cost Ratio (R/C), Break-Even Point (BEP), and Return on Investment (ROI). The method employed was a profitability analysis using revenue theory, applying the R/C, BEP, and ROI formulas to the business's cost and revenue data. The results indicate that from a technical and technological perspective, all operational requirements for the hatchery were met, including location suitability, operational scale, pond management, and resource utilization, supported by a single-level distribution system. Economically, the business showed profitability and business viability. The total revenue reached IDR 79,552,083. The financial analysis yielded an R/C ratio of 1.5, signifying that every Rp1 spent generated IDR 1.5 in revenue. The production break-even point (BEP) was achieved at 12,635,416 fish seeds. It is concluded that the tilapia seed production business is comprehensively feasible and profitable for further development.